2020
DOI: 10.14738/abr.81.7347
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Gender on Adaptive Coping Mechanisms and Financial Stress

Abstract: It is a fact that financial stress impact university students. Given this notion, this research looked at the moderating impact of gender on the adaptive coping mechanism of private university students on their financial stress. The research was a descriptive-correlational design. The study conveniently employed 369 respondents of the primer private university in Ghana (Valley View University), out of a population of 9,000 to answer self-constructed questionnaires with Cronbach Alpha of .806 for adaptive copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Contrarily, the interaction terms indicate that the relationships of distress with task-focused and avoidance coping were not moderated by gender. This lack of moderating effect contradicts the previous findings that reported a significant negative association between adaptive coping and distress among men (46).…”
Section: Gender Moderation Of the Relationship Between Coping And Dis...contrasting
confidence: 97%
See 1 more Smart Citation
“…Contrarily, the interaction terms indicate that the relationships of distress with task-focused and avoidance coping were not moderated by gender. This lack of moderating effect contradicts the previous findings that reported a significant negative association between adaptive coping and distress among men (46).…”
Section: Gender Moderation Of the Relationship Between Coping And Dis...contrasting
confidence: 97%
“…Moreover, research has reported a significant gender moderation effect on the relationship between coping and stress. It was indicated that the use of adaptive coping was associated with decreased distress among men (46).…”
Section: Introductionmentioning
confidence: 99%
“…To gain further insight into the factors that may amplify or attenuate these proposed associations we conducted moderator analyses, and examined sample-based moderators (participant sex, age, and disease duration), and a methodological moderator (type of distress). Because research suggests that the relationship between adaptive coping and lower distress is stronger in women than in men (Hamid et al, 2023), and maladaptive coping is associated with greater distress in women than men (Hamid et al, 2023;Osei-Kuffour & Peprah, 2020;Zukerman et al, 2017), we examined participant sex as a moderator. There is also evidence that the relationship between coping and psychological distress may vary as a function of age (Duangdao & Roesch, 2008;Matt & Dean, 1993), and disease duration (Smári & Valtýsdóttir, 1997), and so all of these were investigated as potential moderators.…”
Section: The Current Studymentioning
confidence: 99%